PENGEMBANGAN BAHAN AJAR KALKULUS VEKTORBERDASARKAN MODEL PEMBELAJARAN MATEMATIKAKNISLEY SEBAGAI UPAYA MENINGKATKAN KOMPETENSI MATEMATIKA MAHASISWA - Dedy, Endang; Mulyana, Endang; Sudihartinih, Eyus (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2012)
This research is a study of Vector Calculus teaching material development that is designed toactivate all parts of students brain in learning process. The purpose of this research is to improve student'sunderstanding on mathematic subject. This teaching material development is based on Knisley'sMathematic Learning Model. The steps in this model of learning are exploration, elaboration, andconfirmation activities as guided in learning process standards.The research method adopted follows a series of research development developmental research)through thought experiments and instruction experimentation. The study begins with an in-depth studytheoretically develop the syllabus according to Vector Calculus curriculum structure and the distributionof subjects contained in the curriculum UPI 2010. The next step compile teaching materials presented inprint media which comes with interactive computer programs.Lectures by using teaching materials and student assignments that have been developed followingthe steps Knisley's Mathematic Learning Model effective in improving student competence in vectorcalculus. This is presumably because the students have the opportunity to develop ideas collaborativelywith peers in completing tasks.Keywords: Knisley's Mathematic Learning Model, exploration, elaboration, confirmation.